Impact of Thermal Mass Oriented Measures Over CO2 Emissions Of a Thermally Insulated Lowrise Apartment Building in Izmir, Turkey - Mümine Gerçek (Konya Technical University Faculty of Architecture and Design, 2015)
Climate change has drawn the attention of many researchers and practitioners to focus on the methods to address the challenges in achieving low-carbon buildings and cities and in future developments. Nevertheless, few studies have explored the impacts of thermal mass applications for the lowest carbon emissions of building operational energy consumption. A comparative study of CO2 emissions due to different wall and floor compositions is presented in accordance with their lifespans for a hot-humid climate site. Aim of this study is to examine the relation between the energy oriented operations and carbon emissions of the building. Firstly, an existing low-rise building in İzmir is selected, then modelled in the dynamic simulation model software DesignBuilder v4 by synchronizing drawings with basic operational principles of the program. Furthermore, various influence factors of building envelope thermal characteristics are selected as follows: type, location, thickness and thermal specifications of materials used by keeping thermal conductivity value constant. At the end, the research presents remarkable influence of thermal mass oriented measures on reducing energy demands and carbon footprints.